Evaluation for an equitable society - Donaldson, Stewart I.; Picciotto, Robert (Evaluation and society., 2016)
Governments and organizations of all shapes and sizes espouse values of equity and social justice. Yet, there are many examples of unfair social arrangements and employment conditions, dysfunctional government practices, and growing income inequality in both developed and developing countries worldwide. The profession and transdiscipline of evaluation is well equipped to address issues of inequality and social injustice, but until recently has been much more focused on primary stakeholder and donor satisfaction (being as useful as possible to funders of interventions and evaluations) and accountability concerns.The authors in this volume challenge the field of evaluation to become more concerned about using evaluation to develop more equitable organizations, governments, and societies. Leading evaluation theorists and practitioners including Michael Scriven, Jennifer Greene, Thomas Schwandt, Emily Gates, Sandra Mathison, Karen Kirkhart, Saville Kushner, Lois-Ellin Datta, Ernest House, Robert Stake, Patricia Rogers, Robert Picciotto and Stewart Donaldson, provide a range of visions for how evaluation can play a much larger role in facilitating social justice across the globe.Evaluation for an Equitable Society will be of great interest to evaluation practitioners, students and scholars. It will be of interest to those teaching and taking introductory evaluation courses, as well as advanced courses focused on improving evaluation theory and practice.